2008
DOI: 10.2174/138161208784041123
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to the Structural Organization of Parasitic Protozoa

Abstract: As eukaryotic cells, protozoa present a classical structural organization where most of the structures and organelles typical of mammalian cells are found. However, even for usual organelles these organisms present structural diversity. In addition, some of the protozoa structures, such as the mitochondria, peroxisomes and even the Golgi complex, are not observed. On the other hand, new organelles such as the hydrogenosomes, mitosomes, Apicoplast, kinetoplast, glycosomes (specialized peroxisomes), rhoptries, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 113 publications
(148 reference statements)
1
22
0
2
Order By: Relevance
“…The uptake of macromolecules by promastigotes occurs through the flagellar pocket, which is an invagination of the plasma membrane, devoid of microtubules. This region is the only place where exocytic and endocytic activity occurs [30]. In promastigotes submitted to drug and/or plant extracts treatments, this increased exocytic activity probably occurs to expel the toxic compound [18, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of macromolecules by promastigotes occurs through the flagellar pocket, which is an invagination of the plasma membrane, devoid of microtubules. This region is the only place where exocytic and endocytic activity occurs [30]. In promastigotes submitted to drug and/or plant extracts treatments, this increased exocytic activity probably occurs to expel the toxic compound [18, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors, using plant products, demonstrated similar kinetoplast alterations [18, 34]. The kinetoplast is a unique organelle present only in trypanosomatid protozoa and is, thus, a potential drug target due to its unique structure and function, which is matched in its mammalian host [24, 30, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Well-known merozoite antigens are the apical membrane antigen 1 (AMA-1) and merozoite surface proteins (MSPs)[3]. These antigens are involved in erythrocyte invasion[4,5] and are important vaccine candidates[6]. Variant surface antigens (VSAs) are important targets of protective immunity[7], but are also responsible for parasite evasion of the immune system by means of clonal antigenic variation [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…In those species that switch from vertebrate to invertebrate hosts, this and other changes may be dramatic, involving the appearance of developmental stages which do not divide and stages which are highly infective through a process generally described as protozoan differentiation or transformation [1, 2]. Among the trypanosomatids, T. cruzi presents one of the most complex life cycles involving several developmental stages found in the vertebrate and the invertebrate hosts as well as in the bloodstream and within vertebrate host cells Figure 1 …”
Section: Introduction To T Cruzi and Its Life Cyclementioning
confidence: 99%